STUDYING THE PUBLIC ADMINISTRATION OF THE RUSSIAN FEDERATION FROM THE PAST: THE SOCIALIST ADMINISTRATIVE TRADITION (Third Sector Social Economic Review, 2023)
This study examines the socialist public administrative tradition, which bases its existence on a different set of ideas than Western socio-economic systems. In this context, the differences in the organizational structure, public personnel system, civil society, political atmosphere, administrative culture, reform principles and financial systems of the socialist tradition are compared with the Western administrative traditions. The main factor that enabled socialist tradition to emerge with a different logic from the Western is based on the idea of sharing wealth equally among individuals through social organizations. The socialist system presents a collective economic model, an economy based on planning and a centralized administrative approach against the Western spirit of capitalism. Centrifugal tendencies such as centralism, totalitarian tendency, dominant bureaucratic class, social composition, culture, nationalism and exclusion of religion from the state power which are embedded in the DNA of Russian public administration today, are basically the legacy of the socialist administrative tradition. Therefore, learning the strengths and weaknesses of such an effective administrative tradition that dominated the twentieth century will contribute to understand the public administration of today's Russian Federation.
Keywords: Socialist Administrative Tradition; Russian Federation Public Administration; Administrative Traditions; Comparative Public Administration; Non-Western Administrative Traditions.